A rare case of ovarian carcinosarcoma with squamous cell carcinoma - Atsushi Daimon; Satoe Fujiwara; Yoshimichi Tanaka; Tomohito Tanaka; Masahide Ohmichi (BMC, 2019)
Abstract Background Ovarian carcinosarcoma, which contains sarcomatous and carcinomatous components, is a very rare tumor. The carcinomatous component is often adenocarcinoma, and squamous cell carcinoma is extremely rare. We herein report a case of ovarian carcinosarcoma in which the carcinomatous component was squamous cell carcinoma. Case presentation A 68-year-old woman presented with a huge ovarian tumor with a clinical diagnosis of malignant tumor of the ovary. She underwent hysterectomy, bilateral adnexectomy, omentectomy and lymphadenectomy. Histologically, the tumor cells showed undifferentiated pleomorphic sarcoma as the sarcomatous component and squamous cell carcinoma as the carcinomatous component. The final diagnosis was ovarian carcinosarcoma with squamous cell carcinoma in the carcinomatous component, stage IIIA1. Postoperatively, the patient was treated with six cycles of combination chemotherapy with paclitaxel and carboplatin as adjuvant therapy. The patient was free of disease at 45 months' follow-up consultation. Conclusion This is a rare report of ovarian carcinosarcoma with an epithelial component composed of squamous cell carcinoma. Combination chemotherapy with paclitaxel and carboplatin may be an effective choice as adjuvant chemotherapy in cases of ovarian carcinosarcoma including squamous cell carcinoma.